2023
DOI: 10.1155/2023/5572754
|View full text |Cite
|
Sign up to set email alerts
|

The Senolytic Drug Fisetin Attenuates Bone Degeneration in the Zmpste24−/− Progeria Mouse Model

Abstract: Aging leads to several geriatric conditions including osteoporosis (OP) and associated frailty syndrome. Treatments for these conditions are limited and none target fundamental drivers of pathology, and thus identifying strategies to delay progressive loss of tissue homeostasis and functional reserve will significantly improve quality of life in elderly individuals. A fundamental property of aging is the accumulation of senescent cells. Senescence is a cell state defined by loss of proliferative capacity, resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…These results suggest that senescent macrophages may play a significant role in the development of muscle dystrophy by impacting the function of muscle stem cells and that the senolytic elimination of these cells may be a promising therapeutic strategy. We have recently shown that the elimination of senescent cells with senolytic treatment (Fisetin) can improve bone health in a progeria animal model that develops premature osteoporosis [40]. Together, these results suggest that senolytics may have the potential for use in the treatment of human age-related musculoskeletal disorders, including OA.…”
Section: Senolytic Agents and Their Functionality In Cellular Senesce...mentioning
confidence: 93%
See 1 more Smart Citation
“…These results suggest that senescent macrophages may play a significant role in the development of muscle dystrophy by impacting the function of muscle stem cells and that the senolytic elimination of these cells may be a promising therapeutic strategy. We have recently shown that the elimination of senescent cells with senolytic treatment (Fisetin) can improve bone health in a progeria animal model that develops premature osteoporosis [40]. Together, these results suggest that senolytics may have the potential for use in the treatment of human age-related musculoskeletal disorders, including OA.…”
Section: Senolytic Agents and Their Functionality In Cellular Senesce...mentioning
confidence: 93%
“…Increased numbers of senescent osteocytes have been observed in both murine and human models [37,38], and induction of senescence in murine and human osteocytes has been shown to increase RANKL-dependent bone resorption [39]. We have recently shown that the elimination of senescent cells with senolytic treatment can improve bone health in a progeria animal model [40]. Senescent cells have also been shown to accumulate in osteoarthritic joints [41][42][43].…”
Section: The Role Of Inflammation and Cellular Senescence In Oamentioning
confidence: 99%
“…Relevant to orthopedic disease , one study found that treatment with dasatinib and quercetin decreased osteoclastic activity while promoting osteoblastic differentiation in mouse models of osteoporosis ( 102 ). Conversely, in another mouse model (accelerated aging Z24–/– model) dasatinib and quercetin treatment did not mitigate trabecular bone loss ( 103 ) while another study indicated dasatinib and quercetin treated mice may actually improve bone production of aged bone marrow derived mesenchymal stem cells ( 104 ). Dasatinib and quercetin treatment have facilitated growth of aged muscles through SC clearance and altered Igf1, Ddit4, Mmp14 gene expression in a mouse model of blunted muscle hypertrophy ( 105 ).…”
Section: Preclinical Evidence For Senotherapeuticsmentioning
confidence: 98%
“…It has been shown to reduce senescence markers in multiple murine and human tissues in a cell type-specific manner, to restore tissue homeostasis, to attenuate age-associated pathologies and to extend lifespan after its administration in progeroid and old mice [ 152 ]. Regarding its beneficial effects against pathological conditions of the musculoskeletal system, fisetin has been shown to counteract osteoporosis in in vitro and in vivo preclinical studies across animal species [ 153 ], to inhibit IL-1β-induced inflammatory response in human OA chondrocytes through activating SIRT1 and to attenuate the progression of OA in mice [ 154 ], as well as to ameliorate bone degeneration in the Zmpste24 −/− progeria murine model for Hutchinson–Gilford progeria syndrome [ 155 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%